Staff Representation Rights Related to The Creation Of Employee Capital Plans (PPK) - Krajewski, Marcin (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The article presents the role of the staff representation under the Act of 4 October 2018 on Employee Capital Plans. Employee Capital Plans (PPK) are the part of third pillar of polish pension system. By creating the PPK, the legislature placed the staff representation and the employer under an obligation to co-decide on the form of the created capital plan. The method of identifying the staff representation, as defined in the Act on Employee Capital Plans, is modelled on the regulation contained in the Act on Occupational Pension Schemes. The Act on Employee Capital Plans states, that an occupational trade union organisation operating within the premises of the company excludes the competence of representation of employees. The legitimacy of the primacy of the trade union over the non-union representation of the staff stems, first of all, from the possibility of guaranteeing the employees’ effective participation in the selection of the financial institution.